2016
DOI: 10.18203/issn.2454-2156.intjscirep20164841
|View full text |Cite
|
Sign up to set email alerts
|

Thrombocytopenia absent radii syndrome in a twenty five day old female neonate: a case report

Abstract: <p class="abstract">Thrombocytopenia absent radii (TAR) is a rare genetic disorder associated with multiple additional anomalies. We report a case of a 25 day old female neonate with thrombocytopenia and bilateral absent radii with flexion of the elbow joint and radial deviation of the wrist joint. TAR, although rare are not uncommon. Thus, we have presented a 25 day old neonate with radiological features of absent radii and fluctuating platelet counts that subsequently showed thrombocytopenia that warra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…It has no gender preference but some studies have reported female's predilection [1]. Like in the index case, 2 previous reports of TAR syndrome by Musa et al and Alao et al from different regions in Nigeria were in females [4,5]. The cause of the thrombocytopenia is still unclear.…”
Section: Discussionmentioning
confidence: 82%
“…It has no gender preference but some studies have reported female's predilection [1]. Like in the index case, 2 previous reports of TAR syndrome by Musa et al and Alao et al from different regions in Nigeria were in females [4,5]. The cause of the thrombocytopenia is still unclear.…”
Section: Discussionmentioning
confidence: 82%